2017
DOI: 10.1038/s41598-017-02853-3
|View full text |Cite|
|
Sign up to set email alerts
|

Population genetics analysis of the Nujiang catfish Creteuchiloglanis macropterus through a genome-wide single nucleotide polymorphisms resource generated by RAD-seq

Abstract: Advances in genome scanning using high-throughput sequencing technologies has led to a revolution in studies of non-model organisms. The glyptosternoid fish Creteuchiloglanis macropterus, is widely distributed in the main stem and tributaries of the Nujiang River basin. Here, we analyzed IIB restriction-site-associated DNA (2b-RAD) sequences and mitochondrial DNA sequences, to assess the genomic signature of adaptation by detecting and estimating the degree of genetic differentiation among ten Creteuchiloglani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 89 publications
0
17
1
Order By: Relevance
“…Indeed, much of our understanding of gene flow and population genetic patterns in fluvial systems comes from studies of fish and aquatic insects (e.g. Faulks, Gilligan, & Beheregaray, ; Finn & Adler, ; Finn, Blouin, & Lytle, ; Fluker, Kuhajda, & Harris, ; Fluker, Kuhajda, Lang, & Harris, ; Kang, Ma, & He, ; Lecaudey, Schliewn, Osinov, Taylor, Bernatchez, Schliewn, & Osinov, ; Robinson, Simmons, Williams, & Moyer, ; Stobie, Oosthuizen, Cunningham, & Bloomer, ). Moreover, hypotheses that predict diversity patterns across riverine landscapes have been mostly developed with data on freshwater insects and fish (reviewed by Davis et al, ; Hughes et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, much of our understanding of gene flow and population genetic patterns in fluvial systems comes from studies of fish and aquatic insects (e.g. Faulks, Gilligan, & Beheregaray, ; Finn & Adler, ; Finn, Blouin, & Lytle, ; Fluker, Kuhajda, & Harris, ; Fluker, Kuhajda, Lang, & Harris, ; Kang, Ma, & He, ; Lecaudey, Schliewn, Osinov, Taylor, Bernatchez, Schliewn, & Osinov, ; Robinson, Simmons, Williams, & Moyer, ; Stobie, Oosthuizen, Cunningham, & Bloomer, ). Moreover, hypotheses that predict diversity patterns across riverine landscapes have been mostly developed with data on freshwater insects and fish (reviewed by Davis et al, ; Hughes et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…RAD sequencing is generally used in marine organisms and plant research, to develop SNP molecular markers, but less applied in insect research. The researchers used this method to analyze the genetic structure and genetic diversity of white perch Morone Americana [15], Nujiang catfish Creteuchiloglanis macropterus [35], American lobster Homarus americanus [36], Sweetpotato Ipomoea batatas [37], and other organisms. All of them obtained good results.…”
Section: Discussionmentioning
confidence: 99%
“…For example, some studies have focused on metabolic rate, as reported in highland westslope cutthroat trout (Oncorhynchus clarkii) as compared with introduced lowland rainbow trout (Oncorhynchus mykiss) in the Oldman River basin (Canada): Fish at high altitudes have a lower metabolic rate [3]. Kang and co-workers [4] investigated the genetic mechanism of high-altitude adaptation in Creteuchiloglanis macropterus (Siluriformes) and found that many genes were involved in energy metabolism and hypoxia, which might be an important resource for studying adaptations to a high-altitude environment. Li and co-workers [5] characterized the mitochondrial genomes of two species ("morphologically primitive" clade and "morphologically specialized" clade) of schizothoracine fishes.…”
Section: Introductionmentioning
confidence: 99%